2005
DOI: 10.1128/iai.73.3.1284-1294.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Metabolism and Systemic Pasteurellosis

Abstract: Pasteurella multocida subsp. multocida is a commensal and opportunistic pathogen of food animals, wildlife, and pets and a zoonotic cause of human infection arising from contacts with these animals. Here, an investigation of multiple serotype A strains demonstrated the occurrence of membrane sialyltransferase. Although P. multocida lacks the genes for the two earliest steps in de novo sialic acid synthesis, adding sialic acid to the growth medium resulted in uptake, activation, and subsequent transfer of siali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 56 publications
(81 reference statements)
0
77
1
Order By: Relevance
“…4). There is also strong genetic evidence that the pm1708-pm1709-encoded TRAP transporter from P. multocida is also involved in uptake of Neu5Ac (Steenbergen et al, 2005) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). There is also strong genetic evidence that the pm1708-pm1709-encoded TRAP transporter from P. multocida is also involved in uptake of Neu5Ac (Steenbergen et al, 2005) (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Sialic acids are also utilized by commensal and pathogenic bacteria in a number of ways; for example, several pathogenic species of bacteria have been shown to sialylate their cell surfaces to mask them from the host immune system (Varki, 1992(Varki, , 2008Vimr & Lichtensteiger, 2002;Vimr et al, 2004). Many bacteria, including Vibrio cholerae, are also able to utilize sialic acid as a sole carbon, nitrogen and energy source (Nees et al, 1976;Vimr & Troy, 1985;Chang et al, 2004;Severi et al, 2005;Steenbergen et al, 2005;Almagro-Moreno & Boyd, 2009a, b;Brigham et al, 2009). Vimr and colleagues showed that three key catabolic enzymes, (i) Neu5Ac lyase/aldolase (NanA), (ii) N-acetylmannosamine kinase (NanK) and (iii) ManNAc-6-phosphate epimerase (NanE), act sequentially to convert sialic acid (Neu5Ac) into N-acetylglucosamine 6-phosphate (GlcNAc-6-P) (Vimr & Troy, 1985;Vimr et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NanA activity has been found in Pasteurella multocida (Drzeniek et al 1972) and a hypothetic gene sequence encoding NanA (Pm1715, GenBank accession no. Q9CKB0) has been identified (Steenbergen et al 2005). Previously, we reported the cloning of a NanA from E. coli K-12 substrain MG1655 (EcNanA) (Yu et al 2004).…”
Section: Reactionmentioning
confidence: 99%
“…The sialic acid residues contribute to a range of important biological functions, including cellular interactions and stabilizing the conformation of glycoproteins and cellular membranes; these residues also expose or mask receptors for ligands, antibodies, or enzymes and contribute to the function and stability of glycoproteins in serum (3,40). Sialidases are implicated in the pathogenicity of some bacteria, including Clostridium perfringens (33), Streptococcus pneumoniae (46), Pasteurella multocida (42), and Pseudomonas aeruginosa (41). They can modify the host's ability to respond to bacterial infection by increasing the susceptibility of immunoglobulin molecules to proteolytic degradation (28).…”
mentioning
confidence: 99%